Established and emerging coronary risk factors in patients with heterozygous familial hypercholesterolaemia. Issue 12 (16th November 2004) - Neil, H A W; Seagroatt, V; Betteridge, D J; Cooper, M P; Durrington, P N; Miller, J P; Seed, M; Naoumova, R P; Thompson, G R; Huxley, R; Humphries, S E
Abstract : Objectives: To assess the clinical and biochemical factors associated with inter-individual variation in susceptibility to coronary artery disease (CAD) in treated heterozygous familial hypercholesterolaemia. Design: A cross sectional study was conducted of 410 patients recruited from six lipid clinics in the UK. Results: CAD was documented in 104 of the 211 men and in 55 of the 199 women with mean ages of onset of 43.1 and 46.5 years, respectively. CAD was significantly more common in men (49% v 28%, p < 0.001) and in patients who had smoked cigarettes versus patients who had never smoked (51% v 28%, p < 0.001). After adjusting for age, sex, and current smoking status, there were no significant differences between patients with or without CAD in lipoprotein(a), homocysteine, fibrinogen, plasminogen activator inhibitor-1, white blood cell count, body mass index, glucose, triglyceride or total cholesterol. However, high density lipoprotein (HDL) cholesterol concentrations were significantly lower in those with CAD (6%, 95% confidence interval (CI) 1% to 11%, p  =  0.03) and this difference was greater in women than men (12% v 2%, p  =  0.041). Conclusions: These results indicate that emerging coronary risk factors appear not to be associated with CAD in adults with treated familial hypercholesterolaemia, but the strong association with smoking suggests that patients should be identified early in childhood and discouraged from ever starting to smoke.